Appropriateness of Antibiotic Use in Enteric fever inpatients in Tertiary Care Hospitals in Western Nepal: A Cross-Sectional Study - Alam, Kadir; Mishra, P; Angsulee, NK (Nepal Journal of Epidemiology, 2013)
Background: Enteric fever, also known as typhoid fever, is a commonly diagnosed disease in Nepal. Globally, enteric fever affects 21.6 million people and causes 216500 deaths annually. Appropriate use of antibiotics is a key element in the successful treatment of enteric fever. Objective: The study was aimed to study antibiotic use and their appropriateness in the patient with Enteric Fever. Methods: A cross-sectional study was carried out in two tertiary-care hospitals viz. Manipal Teaching Hospital (MTH) and Western Regional Hospital (WRH) in western Nepal between Aug- September 2010. Appropriateness in this study was assessed using Medication Appropriateness Index (MAI) criteria which include indication, effectiveness, dosage, correct directions, practical directions, drug-drug interactions, drug-disease interactions, duplication, duration and expense. Results: Mean use of antibiotics in WRH (2.18±0.87) was not significantly different (P = 0.015) from MTH (2.13±1.11). The Cephalosporin group of antibiotics was used widely to treat enteric fever in both hospitals. On average 1.12 Cephalosporin per patient in MTH and 0.93 Cephalosporin per patient in WRH were used. On average, we found that 31.7% in MTH and 39.5% in WRH of patient’s treatments with antibiotics were inappropriate. Other common types of inappropriateness are expensive drugs [90% (MTH), 92% (WRH)] duplication of antibiotics [53% (MTH), 822% (WRH)], prescribing high generation antibiotics [80% (MTH), 89% (WRH)], and practical direction [17% (MTH), 33% (WRH)]. Conclusion: Conclusively, more than thirty percent of patients in both of hospitals treated for enteric fever received inappropriate antibiotics. Hence we recommend future education or managerial intervention to improve appropriateness. DOI: http://dx.doi.org/10.3126/nje.v3i1.8289 Nepal Journal of Epidemiology 2013;3 (1): 236-242